Controle modal aplicado a uma estrutura de 2 graus de liberdade utilizando atuadores eletromagnéticos - Repinaldo, Joana Pereira (2018)
The present work aims at the active control of vibration through electromagnetic actuators in a mass-spring-damper structure with 2 degrees of freedom. The controller design accomplished using two approaches. The first approach involves the control theory applied in the physical coordinate. In the second approach, the controllers were designed in the modal domain. The modal control was employed for it allows the control of the vibration corresponding to a specific mode of vibration. For comparison and validation of the controllers, the structure was constructed and its parameters identified through the inverse problem technique in conjunction with heuristic optimization method, differential evolution. Therefore, it is possible to estimate the unknown parameters of stiffness and damping of the system. Identifying the system parameters it was possible to design the controllers and together with the electromagnetic actuators apply the active vibration control on structure of 2 degrees of freedom. The controller designed in both approaches was the Neuro-Fuzzy controller. The Fuzzy controller was used for comparison purposes. In the experimental control it was not possible to directly measure all the states of the system, generating the need to estimate these states through a state observer. The results were obtained numerically and experimentally, demonstrate the efficiency of the control.